VEGF-C Is a Thyroid Marker of Malignancy Superior to VEGF-A in the Differential Diagnostics of Thyroid Lesions. - Kosma Woliński; Adam Stangierski; Ewelina Szczepanek-Parulska; Edyta Gurgul; Bartłomiej Budny; Elzbieta Wrotkowska; Maciej Biczysko; Marek Ruchala (PLoS ONE, 2016)
Thyroid nodular goiter is one of the most common medical conditions affecting even over a half of adult population. The risk of malignancy is rather small but noticeable-estimated by numerous studies to be about 3-10%. The definite differentiation between benign and malignant ones is a vital issue in endocrine practice. The aim of the current study was to assess the expression of vascular endothelial growth factor A (VEGF-A) and VEGF-C on the mRNA level in FNAB washouts in case of benign and malignant thyroid nodules and to evaluate the diagnostic value of these markers of malignancy.Patients undergoing fine-needle aspiration biopsy (FNAB) in our department between January 2013 and May 2014 were included. In case of all patients who gave the written consent, after ultrasonography (US) and fine-needle aspiration biopsy (FNAB) performed as routine medical procedure the needle was flushed with RNA Later solution, the washouts were frozen in -80 Celsius degrees. Expression of VEGF-A and VEGF-C and GADPH (reference gene) was assessed in washouts on the mRNA level using the real-time PCR technique. Probes of patients who underwent subsequent thyroidectomy and were diagnosed with differentiated thyroid cancer (DTC; proved by post-surgical histopathology) were analyzed. Similar number of patients with benign cytology were randomly selected to be a control group.Thirty one DTCs and 28 benign thyroid lesions were analyzed. Expression of VEGF-A was insignificantly higher in patients with DTCs (p = 0.13). Expression of VEGF-C was significantly higher in patients with DTC. The relative expression of VEGF-C (in comparison with GAPDH) was 0.0049 for DTCs and 0.00070 for benign lesions, medians - 0.0036 and 0.000024 respectively (p<0.0001).Measurement of expression VEGF-C on the mRNA level in washouts from FNAB is more useful than more commonly investigated VEGF-A. Measurement of VEGF-C in FNAB washouts do not allow for fully reliable differentiation of benign and malignant thyroid nodules and should be interpreted carefully. Further studies on larger groups are indicated. However, measurement of VEGF-C on mRNA level can bring important information without exposing patient for additional risk and invasive procedures.